Peranan Supporting Psikis Tenaga Medis Terhadap Pengendalian Kecemasaan Pasien COVID-19 Yang Menjalani Isoman Di Rumah - reza adityas trisnadi; rizkie woro hastuti; Elly Noerhidayati; Warsiyah (Midwifery Department of Sultan Agung Islamic University of Semarang, 2022)
A great influence on public health is caused by the COVID-19 pandemic, starting from the physical to the psychological community. When someone is confirmed to have COVID-19, anxiety about many things caused by this dangerous virus haunts everyone. Anxiety begins with a threatening situation as a dangerous stimulus. At a certain level, anxiety can make a person more alert to a threat, because if it is felt that the threat is considered harmless, then a person will not do self-defense. Anxiety needs to be managed properly so as not to cause excessive panic. Excessive anxiety will affect the body's immune system and affect the healing rate of COVID-19. The method used is an observational design with a cross-sectional design. This study is only to observe observational results using Zung's questionnaire on COVID-19 sufferers who are self-isolating at home.